Design and Validation of a Dielectric Method-Based Composite Material Curing Monitoring Platform - Wenfeng Yang; Xinguang Yin; Shaolong Li; Shuaicai Liu; Ran Zhang; Yu Cao; Bowen Yang; Hongshuai Huang (Sensors)
Monitoring the curing process is crucial for guiding and optimizing the curing procedures of composite material repair patches. Traditional embedded online monitoring methods are limited in their ability to track the curing process of these patches. This paper presents a composite material curing monitoring platform designed using dielectric methods. It integrates temperature control, pressure control, dielectric signal acquisition, control and display modules, and is specifically tailored for bag molding curing of repair patches. The platform measures the ionic viscosity of T300 2019B composites, analyzes the curing index, and correlates it with DSC-cured degree tests. The results indicate that the multiple ionic viscosity curves obtained from monitoring exhibit consistent trends, with correlation coefficients between curves exceeding 0.96. The changes in curing index align with the changes in curing degree, demonstrating that the platform can reliably and accurately monitor the ionic viscosity of repair patches. This platform enables effective monitoring of the ionic viscosity during the curing process of composite material repair patches.